Photochemoprotective effects of Spirulina platensis extract against UVB irradiated human skin fibroblasts - Sariya Mapoung (2020)
© 2020 SAAB Ultraviolet B (UVB) irradiation is an important cause of a number of harmful side effects such as sunburn, photoaging, pigmentation and skin cancer. Photoprotection, which is used to prevent UVB interaction and to attenuate UVB related damage could be used to prevent the effects of UVB irradiation. Recently, the use of natural products as skin photoprotective agents has been in increasing demand. In this study, we are proposing a panel of in vitro methods for the evaluation of Spirulina platensis extract for its ability to absorb the UVB spectra by determination of its spectrophotometric Solar Protection Factor (SPF), and by attenuating its biological protective effects against UVB-irradiated human skin fibroblast cultures. Our data revealed that S. platensis extract contained high amounts of phenolic compounds (23,465.71 ± 167.72 mg GAE/kg extract) and produced a high degree of absorbance within a wavelength range of 290–320 nm yielding an SPF value of 30.39 ± 3.37 (3 mg/ml), all of which collectively confirmed the photoprotective activity of S. platensis polyphenols. S. platensis extract has no cytotoxicity on UVB irradiation of human skin fibroblasts, peripheral blood mononuclear cells and red blood cells. It was also found to exert antioxidant activities both in vitro and by way of intracellular reactive oxygen species in UVB irradiation fibroblast cells. The induction of interleukin- 6 and -8 secretions by UVB irradiation was dramatically aborted after S. platensis extract treatment. Moreover, the S. platensis extract significantly inhibited tyrosinase activity. Our above results indicated the photochemoprotective effects of S. platensis extract against UVB irradiation in human skin fibroblast cells. Therefore, S. platensis extract could be considered a prospective source of UVB-absorbers with antioxidant capacity. It could also serve as an additive in photoprotective cosmetic formulations which could prevent the harmful effects of UVB radiation.